Przekształcenia infrastruktury uzdrowisk sudeckich w latach 1945–1966 - Woźniakowska, Kinga (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The subject of the article are postwar transformations of architecture and space of health resorts in Sudetes (Sudety Mountains) taken over by Polish authorities in 1945. Particular emphasis was put on studying the process of using the developed infrastructure of local health resorts, which has left a considerable mark on shaping the entire postwar health resort services
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne